Sleep quality change after upper airway surgery in obstructive sleep apnea: Electrocardiogram‐based cardiopulmonary coupling analysis. (3rd February 2015) - Choi, Ji Ho; Thomas, Robert J.; Suh, Soo Yeon; Park, Il Ho; Kim, Tae Hoon; Lee, Sang Hag; Lee, Heung Man; Yun, Chang‐Ho; Lee, Seung Hoon
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To test the effect of upper airway surgery on sleep quality in adults with obstructive sleep apnea (OSA) and the potential usefulness of electrocardiogram (ECG)‐based cardiopulmonary coupling (CPC) analysis as metrics of sleep quality. Study Design Retrospective outcome research. Methods A total of 62 consecutive adult patients with OSA, consisting of 36 with successful and 26 with unsuccessful outcomes, were included in the study. Mean age was 37.7 ± 8.9 years, and body mass index (BMI, kg/m2) was 26.9 ± 2.3. We compared clinical characteristics (age, BMI, and Epworth Sleepiness Scale [ESS]), sleep (sleep efficiency, stage non–rapid eye movement [N]1, N2, N3, rapid eye movement, and arousal index [ArI]), respiratory (apnea index [AI], apnea‐hypopnea index [AHI], and minimum arterial oxygen saturation [SaO2]), and CPC (high‐frequency coupling [HFC], low frequency coupling [LFC], very–low‐frequency coupling, and elevated low‐frequency coupling [e‐LFC]) parameters between the success and nonsuccess groups before and after surgery. Surgical success was defined when the postoperative AHI was both <20 per hour and 50% of the preoperative value. Results Sleep quality measured by CPC analysis improved significantly (HFC, P = .001; LFC, P = .002; e‐LFC, P = .003), along with parallel reduction in ESS, respiratory parameters (AHI, AI, minimum SaO2), and sleep fragmentation (ArI) in the group with surgical success after upper airway surgery. Conclusions Successful upper airway surgery can improve objective sleep quality in adult patients with OSA. CPC metrics of sleep quality are potentially useful to monitor therapeutic responses during long‐term postoperative follow‐up, as the ECG‐based analysis is available as a standalone option outside laboratory polysomnography. Level of Evidence 4 Laryngoscope, 125:1737–1742, 2015